Analysis of Aloe Vera Plasma Parameters Using Optical Emission Spectroscopy - Kazim, Weam Aqeel; Ali, Alyaa Hussein (Iraqi Journal of Physics, 2025)
Optical emission spectroscopy (OES) is used to analyze the main properties of aloe vera plasma, where the plasma is generated using a plasma jet. Several parameters of the plasma are measured, including electron temperature (Te), electron density (ne), plasma frequency (fp), Debye length (λD), and Debye number (ND). The study is based on the use of different laser energies ranging from 100 to 400 mJ. To evaluate the electron temperature, the Boltzmann scheme was applied, which is based on the analysis of the spectral intensity of optical emissions from the plasma. The electron density was calculated using Stark line broadening, which reflects the effect of electric fields generated by electrons in the plasma on the width of the spectral lines. In this experiment, the target (aloe vera material) was exposed to the laser from a distance of 8 cm, while the emitted radiation was measured using an optical fiber at a distance of 0.5 cm from the target. All measurements were performed in air, where the electron temperature was found to range between 0.793 and 1.124 eV. The results showed that both the electron temperature and the electron density increased with increasing laser power. This increase is in line with expectations, as higher laser power leads to greater detuning of matter and an increase in the number of electrons generated in the plasma, which increases the plasma density and temperature.